Detection of Antibodies Against Melioidosis from Animal Sera in Thailand by Indirect Haemagglutination Test - Nittaya Srikawkheaw; Ong-ard Lawhavinit (Agriculture and Natural Resources, 2007)
Antibody detection against melioidosis from 8,153 serum samples of cattle, sheep, goats, pigs and deers of 18 provinces in Thailand was done by using indirect haemagglutination test during the year 2005-2006 (6,576 goat sera , 1,050 pig sera, 78 cattle sera , 83 deer sera and 366 sheep sera). Serum antibodies titer at ≥ 1:160 against melioidosis were found in goats (0.33%), pigs (7.23%), cattle (2.56%), deers (7.23%) and sheep (6.83%), however, more information is needed for the conclusion of this study.